Pigmented epithelioid melanocytoma: A clinico-histopathological enigma - Pooja Dilip Shah; Raju G Chaudhary; Ashish Jagati; Kalgi D Baxi (Wolters Kluwer Medknow Publications, 2022)
Blue nevi are a group of congenital or acquired benign dermal melanocytic tumors. Various clinical and histological variants have been described.Epithelioid blue nevus (EBN), an uncommon variant may present as blue gray nodule over trunk, extremities which might occur either sporadically or in association with Carney complex. Due to clinical and histological overlap with other pigmented melanocytic lesions clinicopathological correlation is essential. We report a case of epithelioid blue nevus on dorsum of right foot in a 22-year-old man.